Look around! : a book about shapes - Fisher, Leonard Everett (New York, N.Y., U.S.A. : Puffin Books, 1989)
Presents basic geometrical shapes in familiar scenes for the reader to identify.
Reprint. Originally published: New York, N.Y. : Viking Kestrel, 1987.
Booklist.
Bulletin (Center for Children's books).
1.3
K-3
Keywords: Geometry -- Juvenile literature; Geometry; Shape; Shape; Size; Geometry; Shape